Effect of freshwater advection and winds on the vertical structure of chlorophyll in the northern Bay of Bengal. (September 2020) - Amol, P.; Vinayachandran, P.N.; Shankar, D.; Thushara, V.; Vijith, V.; Chatterjee, Abhisek; Kankonkar, A.
Abstract: The northern Bay of Bengal receives a large amount of fresh water through river runoff and rainfall during the Indian summer monsoon (June–September). This fresh water spreads offshore and can modulate the upper-ocean chlorophyll via two processes: advection of river nutrients and inhibition of vertical supply of subsurface nutrients by increasing the stratification. We address these two processes during the summer monsoon of 2012 using hydrographic observations and a coupled physical-biogeochemical model. The observations show an increase in surface chlorophyll associated with the advection of a freshwater plume on the shelf. Near the slope, but over a cross-shore distance of ~ 70 km, a thin layer separates this elevated surface chlorophyll from the subsurface chlorophyll maximum layer (SCML). This separation disappears as the freshwater plume reaches the open ocean. The SCML shoals toward the coast and is absent on the shelf. Time-series observations from the open ocean also show an increase in chlorophyll in concurrence with the arrival of a freshwater plume. Simulations with a coupled physical-biogeochemical model show, however, that it is the wind-induced vertical processes that cause the increase in chlorophyll in the open ocean and not the nutrients brought by the horizontal advection of freshwater plumes. The increase in stratification only limits and does not completely inhibit the vertical supply of nutrients from the subsurface layers.